2017
DOI: 10.1371/journal.pone.0189968
|View full text |Cite
|
Sign up to set email alerts
|

Integrated self-regulating resistive heating for isothermal nucleic acid amplification tests (NAAT) in Lab-on-a-Chip (LoC) devices

Abstract: Isothermal nucleic acid amplification tests (NAAT) in a Lab-on-a-Chip (LoC) format promise to bring high-accuracy, non-instrumented rapid tests to the point of care. Reliable rapid tests for infectious diseases allow for early diagnosis and treatment, which in turn enables better containment of potential outbreaks and fewer complications. A critical component to LoC NAATs is the heating element, as all NAAT protocols require incubation at elevated temperatures. We propose a cheap, integrated, self-regulating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The "self-regulating" heaters had average initial resistances of 0.8 Ohms and average steady-state resistance (heatedup) of 13.6 Ohms which ultimately required 3 V of DC power to reach 61.5-64°C. 47 In our work, a single 5.5 Ohm microheater was heated for 15 minutes for ten trials and produced heat curves with no significant difference between heating trials and standard deviations between 4.3 and 4.9 within the trials (Fig. 4E, Tables S4 and S5 †).…”
Section: Printed Microheater Characterization and Design Analysismentioning
confidence: 67%
See 3 more Smart Citations
“…The "self-regulating" heaters had average initial resistances of 0.8 Ohms and average steady-state resistance (heatedup) of 13.6 Ohms which ultimately required 3 V of DC power to reach 61.5-64°C. 47 In our work, a single 5.5 Ohm microheater was heated for 15 minutes for ten trials and produced heat curves with no significant difference between heating trials and standard deviations between 4.3 and 4.9 within the trials (Fig. 4E, Tables S4 and S5 †).…”
Section: Printed Microheater Characterization and Design Analysismentioning
confidence: 67%
“…Because there is no resistance drift for these resistors, we can easily maintain both temperature and power settings. Pardy et al evaluated commercial prototype elements and maintained temperature between 60-63°C for 25 minutes 47 featuring heating elements that increase in resistance with temperature. They claimed this resistance drift made the heaters self-regulating.…”
Section: Printed Microheater Characterization and Design Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…We compared the performance of a commercially available self-regulating heating element to a thermostat-regulated etched foil heating element in LoC NAAT prototypes and concluded that self-regulating heating was the favorable option for disposable instrument-free LoC NAAT devices [ 33 ]. Furthermore, we demonstrated a self-regulating heater integrated with a LoC prototype system, with which we performed loop-mediated isothermal amplification (LAMP) in the 20–25 °C room temperature range [ 34 ]. In this work, we introduce the concept device of our instrument-free LoC NAAT platform and perform thermal analysis on it to verify that it is capable of supporting LAMP in the expected end-user environment.…”
Section: Introductionmentioning
confidence: 99%